Using Albumin Denaturation Inhibition Method to Determine the Anti-Inflammatory Activity of Phenolic Compounds in Some Locally Available Fruit Juices (Latakia University Journal -Medical Sciences Series, 2021)
Fruit Juices are considered as an important source of phenolic compounds. Three natural Black mulberry, Pomegranate and orange juices were selected to determine their phenolic content and assess their anti-inflammatory activity. A phenolic extract for each juice was also prepared. Total Phenolic content was determined using Folin-Ciocalteu method. The anti-inflammatory activity was evaluated using albumin denaturation inhibition method at concentration of phenolic compounds ranged between (10- 60 µg/ml). Ibuprofen was used as a standard drug.Phenolic content in juices was higher than their phenolic extracts. The highest total phenolic content was found in black mulberry juice and its phenolic extract. Black mulberry juice and its phenolic extract also revealed the highest anti-inflammatory activity among the studied juices. Phenolic extracts showed higher anti-inflammatory activity than the juices at the same concentration of phenolic compounds.